(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the issues of improving the pedagogical foundations for preparing boys for independent family life. The study analyzes the scientific and theoretical bases of family life preparation, identifies pedagogical conditions, and develops a model aimed at increasing the effectiveness of this process. An experimental study was conducted among 10th–11th grade male students of secondary schools, and the results were evaluated using mathematical and statistical methods. The findings demonstrate that the improved pedagogical approach effectively contributes to the development of family responsibility, conscious attitudes toward marriage, and social competencies among boys. The results of the study have practical significance for organizing educational activities within schools, families, and local communities.